2022
DOI: 10.13057/biodiv/d230713
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of mangrove health index on three genera dominated zones in Benoa Bay, Bali, Indonesia

Abstract: Abstract. Sugiana IP, Andiani AAE, Dewi IGAIP, Karang IWGA, As-Syakur AR, Fharmawan IWE. 2022. Spatial distribution of mangrove health index on three genera dominated zones in Benoa Bay, Bali, Indonesia. Biodiversitas 23: 3407-3418. A study of mangrove forest stratification was conducted in Benoa Bay which experienced high coastal development pressures during the last decade. The study aimed to determine mangrove health index distribution (MHI) and forest community structures along three genera-dominated zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
3
1
4
Order By: Relevance
“…Five genera-dominated zones were identified from the estuarine habitat, while only three obvious patterns of mangrove-occupied oceanic habitat were recorded. The number of genera-dominated layers in this study was higher than the estuarine mangrove in Benoa Bay, which was composed of three mangrove zones (Sugiana et al 2022). Another study in an archipelagic area of Papua found three zones along the mangrove area perpendicularly from landward to seaward (Nurdiansah and Dharmawan 2021a).…”
Section: Distribution Of Mangrove Genera-dominated Zonescontrasting
confidence: 45%
“…Five genera-dominated zones were identified from the estuarine habitat, while only three obvious patterns of mangrove-occupied oceanic habitat were recorded. The number of genera-dominated layers in this study was higher than the estuarine mangrove in Benoa Bay, which was composed of three mangrove zones (Sugiana et al 2022). Another study in an archipelagic area of Papua found three zones along the mangrove area perpendicularly from landward to seaward (Nurdiansah and Dharmawan 2021a).…”
Section: Distribution Of Mangrove Genera-dominated Zonescontrasting
confidence: 45%
“…Analisis spasial MHI dilakukan dengan menggunakan kombinasi 4 index vegetasi berdasarkan persamaan yang dikembangkan oleh Nurdiansah & Dharmawan (2021). Formula perhitungan yang sama juga digunakan pada penelitian lainnya antara lain Sugiana et al (2022) dan Dharmawan (2021). Secara umum terjadi perbaikan kondisi hutan mangrove berdasarkan nilai MHI di kawasan pesisir Surabaya dan Sidoarjo.…”
Section: Analisis Mangrove Health Index (Mhi)unclassified
“…Tidak adanya ancaman pembalakan liar, konversi lahan dan reklamasi pantai memungkinkan hutan mangrove tumbuh semakin luas. Jika dibandingkan dengan penelitian serupa yang dilakukan di Teluk Benoa Bali (Sugiana et al, 2022) dapat dinyatakan bahwa berdasarkan perhitungan MHI, maka kondisi hutan mangrove di pesisir Surabaya dan Sidoarjo menunjukkan trend yang lebih baik. Penurunan kualitas hutan mangrove di Teluk Benoa terpantau dari semakin bertambahnya luasan dengan kelas MHI buruk.…”
Section: Struktur Komunitas Mangroveunclassified
See 1 more Smart Citation
“…We took three stations divided by mangrove community zones (seaward, middle and landward), during the rainy season in December 2020, with atmospheric geographical conditions in the form of temperatures ranging from 25.1°C -32.2°C (Average: 28.0°C) and rainfall of 355.5 mm in the same month [11]. Overall, three mangrove genera predominate in this area: Sonneratia, Rhizophora and Bruguiera [10,13], with an average mangrove health index condition in the moderate category [13]. Environmental factors such as the type of sediment range from fine sand to gravel with a predominance of coarse sand [14,15], as well as trends in shaft water quality (salinity and pH) which experience gradations with differences in distance from the sea [10].…”
Section: Site Descriptionmentioning
confidence: 99%